(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
World experience shows that one of the important areas of development of the budget-tax system is to strengthen the financial independence of local budgets. This issue is primarily related to the stability and strength of their income bases, including tax income bases. In turn, local budgets ensure the stability of tax revenue bases, firstly, socio-economic development of the country’s regions and ensure the interests of the residents of the respective regions, to further improve their lives, and to create favorable conditions for increasing the standard of living and well-being, and secondly , allows for the rational use of natural raw materials, production and labor potential in the region, as well as the expansion of the powers of local state authorities. In most "developed and developing countries, local budget revenues occupy a significant share of state budget revenues. In particular, this indicator is 30% in Japan, 33% in Great Britain, 34% in Austria, 38% in France, 39% in Portugal, 58% in Norway, 60% in Luxembourg. This has a positive effect on the development of the world economy.